Carbon felt-based Ni-coated UiO-66 / GO catalytic electrode, preparation method and application thereof, and product containing carbon felt-based Ni-coated UiO-66 / GO catalytic electrode

By using carbon felt-based Ni@UiO-66/GO catalytic electrodes in bioelectrochemical systems, the problems of low BES recovery efficiency, single metal types and high cost of electrode materials in the prior art are solved, and efficient heavy metal removal and recycling are achieved.

CN119797511APending Publication Date: 2025-04-11LIAONING UNIVERSITY OF PETROLEUM AND CHEMICAL TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510009954.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing bioelectrochemical systems (BES) have problems with low recycling efficiency, single metal types and high cost of precious metal electrode materials in handling organic pollutants and heavy metal recycling.

Method used

A carbon felt-based Ni@UiO-66/GO catalytic electrode was used. This electrode was supported on a carbon felt by hydrothermal synthesis to prepare a catalytic electrode with high electrochemical properties.

Benefits of technology

It significantly improves the electrochemical performance of the bioelectrochemical system, promotes the active growth of microorganisms, and efficiently removes and recovers heavy metal ions emitted in the electroplating process of printed circuit boards through the combined action of electroreduction and electroflocculation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797511A_ABST
    Figure CN119797511A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-felt-based Ni-coated UiO-66 / GO catalytic electrode, a preparation method and application of the carbon-felt-based Ni-coated UiO-66 / GO catalytic electrode, and a product containing the carbon-felt-based Ni-coated UiO-66 / GO catalytic electrode, and belongs to the technical field of sewage purification and wastewater resource utilization. Comprising the following steps: jointly loading Ni-coated UiO-66 and graphene oxide on a carbon felt by utilizing hydrothermal synthesis to prepare the carbon felt-based Ni-coated UiO-66 / GO catalytic electrode, wherein the molar ratio of a nickel source to a zirconium source in the Ni-coated UiO-66 is 1: 3. The carbon felt-based Ni-coated UiO-66 / GO catalytic electrode (Ni-coated UiO-66 / GO-CF) prepared by the preparation method disclosed by the invention is applied to a stacked bioelectrochemical system as a cathode material, and has an obvious promotion effect on an oxidation-reduction reaction of the electrode; the method is used for treating heavy metal wastewater discharged in a printed circuit board electroplating process, and typical heavy metal elements can be completely removed basically.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sewage purification and wastewater resource utilization, and in particular relates to a carbon felt-based Ni@UiO-66 / GO catalytic electrode and a preparation method, application and products containing the same. Background Art

[0002] Bioelectrochemical system (BES) is a green wastewater treatment technology that can simultaneously achieve pollutant degradation and electrical energy output. This technology will spontaneously generate bioelectricity in the process of treating organic pollutants, and this electrical energy can be directly used for the recovery of heavy metal ions. Its working principle is actually redox: anaerobic microorganisms in the anode chamber oxidize and remove organic matter in the wastewater through metabolism, and produce protons and electrons. Protons enter the cathode chamber through the proton exchange membrane, and electrons flow into the cathode along the wire, so that a potential difference is generated between the anode and cathode, and electrical energy is generated in the system. The electron acceptor in the cathode chamber, such as oxygen, obtains electrons and is reduced to water. If metal ions are used instead of oxygen as the electron acceptor of the cathode, heavy metal ions are converted from soluble forms to less toxic insoluble forms, and heavy metal recovery by BES can be achieved. Studies have shown that it is feasible to use BES technology to treat or recover heavy metals, but there are still problems such as low recovery efficiency, single type of recovered metals, and high cost of precious metal electrode materials.

[0003] Therefore, there is an urgent need to further explore how to use BES to remove pollutants from water more efficiently, stably and at a lower cost. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a carbon felt-based Ni@UiO-66 / GO catalytic electrode and a preparation method, application and products containing the same.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode comprises the following steps:

[0008] The carbon felt-based Ni@UiO-66 / GO catalytic electrode is prepared by co-loading Ni@UiO-66 and graphene oxide on carbon felt using hydrothermal synthesis;

[0009] Wherein, the molar ratio of the nickel source to the zirconium source in the Ni@UiO-66 is 1:3.

[0010] Preferably, the preparation method comprises the following steps:

[0011] The nickel source, the zirconium source and terephthalic acid are uniformly mixed in an organic solvent to obtain a Ni@UiO-66 precursor solution;

[0012] Adding graphene oxide to the Ni@UiO-66 precursor solution and mixing evenly to obtain a mixed solution;

[0013] The pretreated carbon felt is immersed in the mixed solution, and hydrothermal reaction, cooling, washing and drying are carried out in sequence to obtain the carbon felt-based Ni@UiO-66 / GO catalytic electrode (i.e., Ni@UiO-66 / GO-CF).

[0014] Further, the nickel source is nickel chloride; and / or

[0015] The zirconium source is zirconium chloride; and / or

[0016] The organic solvent is N,N-dimethylformamide.

[0017] Furthermore, the Ni@UiO-66 precursor solution needs to use benzoic acid as a pH regulator.

[0018] Furthermore, the pretreatment process is: washing the carbon felt in HCl solution, ethanol and deionized water in sequence, and then ultrasonicating in deionized water for 30 minutes. The concentration of the HCl solution is 1M.

[0019] Furthermore, the conditions in the hydrothermal reaction process are: the hydrothermal reaction temperature is 120° C. and the time is 48 hours.

[0020] Furthermore, the conditions in the drying process are: vacuum drying at 50-60° C. to constant weight.

[0021] The second technical solution of the present invention:

[0022] A carbon felt-based Ni@UiO-66 / GO catalytic electrode is prepared by the above preparation method.

[0023] The third technical solution of the present invention:

[0024] The application of the carbon felt-based Ni@UiO-66 / GO catalytic electrode in the field of preparing bioelectrochemical systems.

[0025] Beneficial effects: The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared by the present invention can be applied to a stacked bioelectrochemical system to significantly improve its electrochemical performance and promote the active growth of microorganisms.

[0026] The fourth technical solution of the present invention:

[0027] The carbon felt-based Ni@UiO-66 / GO catalytic electrode is used in the field of heavy metal wastewater treatment in printed circuit board electroplating process.

[0028] Beneficial effects: The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared by the present invention is applied to a stacked bioelectrochemical system. The catalytic electrode provides reduction sites for heavy metal ions discharged in the electroplating process of printed circuit boards. The copper, nickel, zinc and cadmium elements in the wastewater can be effectively reduced through the combined action of electroreduction and electrocoagulation, thereby achieving efficient removal and recovery of heavy metal ions in the wastewater.

[0029] The fifth technical solution of the present invention:

[0030] A stacked bioelectrochemical system uses the carbon felt-based Ni@UiO-66 / GO catalytic electrode as a cathode.

[0031] Beneficial effects: The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared by the preparation method of the present invention can be used as a cathode electrode in a bioelectrochemical system and can efficiently treat wastewater from the electroplating process of printed circuit boards. The strong interaction between Zr(IV) and carboxylates enables the cathode material to adapt to acidic environments; the introduction of transition metal nodes enhances metal-metal interactions and reduces costs; GO (graphene oxide) contains a large number of oxygen-containing functional groups, which improves the efficiency of cathode redox reactions.

[0032] Preferably, the stacked bioelectrochemical system comprises: a first system and a second system, both systems comprising an anode chamber, a proton exchange membrane and a cathode chamber, wherein the anode chamber and the cathode chamber are separated by a proton exchange membrane; wherein the anode in the anode chamber and the cathode in the cathode chamber are connected by a titanium wire and an external resistor to form a complete circuit.

[0033] Furthermore, the first system includes an anode chamber, a cathode chamber and an air contact oxidation tank, wherein the cathode chamber and the anode chamber are separated by a proton exchange membrane; the air contact oxidation tank has the following functions: first, to create an anaerobic environment to enrich the species of bacteria; second, to dissolve oxygen in the air to relieve the aeration pressure of the cathode chamber;

[0034] The second system includes an anode chamber and a cathode chamber, wherein the cathode chamber and the anode chamber are separated by a proton exchange membrane;

[0035] In the entire stacked bioelectrochemical system, the water flow path is: the first system (anode chamber-air contact oxidation tank-cathode chamber)-the second system (anode chamber-cathode chamber); the two systems are connected by pipelines, and the water flow is transported by the power of the pump.

[0036] Further, the anode chambers in the first system and the second system include a main anode and an auxiliary anode;

[0037] The main anode is an iron anode, and the auxiliary anode is a graphite particle and an activated carbon mixed particle (the volume ratio of graphite particles to activated carbon particles is 1:1, and the particle size is 3-5 mm) filled (filling rate is 90%, the volume percentage of the whole bacterial solution to the mixed particles) with electrogenic bacteria (the main electrogenic bacteria are Gammaproteobacteria and Bacteroidia, and the bacterial solution concentration is 4-8 g / L);

[0038] Furthermore, the cathode chamber includes a cathode having the carbon felt-based Ni@UiO-66 / GO catalytic electrode as a cathode.

[0039] Compared with the prior art, the present invention has the following advantages and technical effects:

[0040] The carbon felt-based Ni@UiO-66 / GO catalytic electrode (Ni@UiO-66 / GO-CF) prepared by the present invention is used as a cathode material in a stacked bioelectrochemical system, which has a significant promoting effect on the electrochemical performance of the electrode. At the same time, the catalytic electrode, as a reduction site for copper, nickel, zinc and cadmium ions, can effectively reduce metal ions in wastewater and achieve efficient removal and recovery of typical heavy metal ions in the electroplating process. Among them, the 3D flower-like structure of GO further increases the specific surface area of ​​the electrode. When Zr 2+ and Ni 2+ The optimal catalytic effect on ORR is achieved when the molar ratio of is 3:1. This electrode is used to treat heavy metal wastewater discharged in the electroplating process of printed circuit boards, and can basically achieve complete removal of typical heavy metal elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0042] Figure 1 The cyclic voltammograms of the carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 and the catalytic electrodes prepared in Comparative Examples 1 and 2, wherein the abscissa represents voltage in V, the ordinate represents current in A, the scan rate is 10 mV / s, and the scanning is performed in 1 mol / L Na2SO4;

[0043] Figure 2 The changes in the ORR starting potential of the carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 and the catalytic electrodes prepared in Comparative Examples 1 and 2 at different Ni doping ratios;

[0044] Figure 3The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 was applied to a stacked bioelectrochemical system to recover different metals in mixed wastewater containing heavy metal ions;

[0045] Figure 4 The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 is used to recover different metals in heavy metal ion mixed wastewater with a total metal ion concentration of 60 mg / L. DETAILED DESCRIPTION

[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0047] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0051] The present invention provides a method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode, comprising the following steps:

[0052] (1) CF pretreatment: wash and dry the cut carbon felt for later use;

[0053] (2) Preparation of carbon felt-based Ni@UiO-66 / GO catalytic electrode:

[0054] First, the nickel source, zirconium source and ligand are uniformly mixed in an organic solvent to obtain a Ni@UiO-66 precursor solution; then, graphene oxide is added and further mixed; finally, the CF obtained in step (1) is placed in the above uniform solution for hydrothermal reaction, and after the reaction is completed, it is cooled to room temperature, washed and dried to obtain a carbon felt-based Ni@UiO-66 / GO catalytic electrode, named Ni@UiO-66 / GO-CF.

[0055] In some preferred embodiments, in step (1), the washing process is: the cut carbon felt is rinsed in HCl solution, anhydrous ethanol and deionized water in turn and ultrasonicated for 30 minutes.

[0056] In some preferred embodiments, in the method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode, in step (2), the nickel source is nickel chloride, the zirconium source is zirconium chloride, the ligand is terephthalic acid, the solvent is N,N-dimethylformamide, and benzoic acid is used to adjust the pH.

[0057] In some preferred embodiments, in the method for preparing the carbon felt-based Ni@UiO-66 / GO catalytic electrode, in step (2), the molar ratio of the nickel source to the zirconium source is 1:3.

[0058] In some preferred embodiments, in the method for preparing the carbon felt-based Ni@UiO-66 / GO catalytic electrode, in step (2), the hydrothermal reaction temperature is 120° C. and the time is 48 h.

[0059] In some preferred embodiments, in the method for preparing the carbon felt-based Ni@UiO-66 / GO catalytic electrode, in step (2), the pretreated carbon felt is rolled up into a column and placed upright in a reactor so that it is completely immersed below the liquid surface of the mixed solution.

[0060] In some preferred embodiments, in the method for preparing the carbon felt-based Ni@UiO-66 / GO catalytic electrode, in step (2), the catalytic electrode is dried at 60° C. in a vacuum environment.

[0061] A carbon felt-based Ni@UiO-66 / GO catalytic electrode is prepared by the above method.

[0062] A stacked bioelectrochemical system using the carbon felt-based Ni@UiO-66 / GO catalytic electrode as a cathode.

[0063] The stacked bioelectrochemical system consists of two systems, each of which contains two anode chambers and two cathode chambers. The wastewater flows through the first system for primary treatment and then enters the second system for secondary treatment.

[0064] The above-mentioned carbon felt-based Ni@UiO-66 / GO catalytic electrode or stacked bioelectrochemical system is used to treat printed circuit board electroplating process wastewater.

[0065] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0066] The raw materials used in the present invention are all purchased from the market. Modified graphene (GO) was purchased from Dazhan Nano (Guangdong) Co., Ltd.; carbon felt was purchased from Yixing Ruibang High-Performance Fiber Products Factory; the electrogenic mixed bacteria were taken from the anaerobic pool sludge mixed liquid of Yantai Xinanhe Sewage Treatment Plant. The electrogenic bacteria were tested and analyzed to be mainly Gammaproteobacteria and Bacteroidia. The electrogenic bacteria were stored in a dark room in a laboratory thermostat at a constant temperature of 20°C, and graphite / activated carbon mixed particles were inoculated (graphite: activated carbon volume ratio of 1:1, particle size 3-5mm), and the total concentration of the bacterial liquid after culture was 4-8g / L.

[0067] The technical solution of the present invention is further illustrated by the following embodiments.

[0068] Example 1

[0069] Pretreatment of CF: The carbon felt was cut into small pieces of 3×4×0.5 cm, and washed with 1 mol / L HCl, anhydrous ethanol, and deionized water in turn, and ultrasonically washed with deionized water for 30 min to make its surface free of dust and no carbon fiber fibers falling off; then dried in a 60°C forced air drying oven for use.

[0070] Preparation of carbon felt-based Ni@UiO-66 / GO catalytic electrode:

[0071] 0.9mmol ZrCl4, 0.3mmol NiCl2·6H2O and 1.2mmol terephthalic acid were added to 40mL N,N-dimethylformamide, and stirred at 350rpm for 30min using a magnetic stirrer to mix the solution evenly, 40mL 0.3mol / L benzoic acid solution was added, and stirred at 350rpm for 120min using a magnetic stirrer to mix the solution evenly, to obtain a Ni@UiO-66 (Zr∶Ni=3∶1) precursor solution;

[0072] Then, 0.22 g / L GO was added, and a magnetic stirrer was used to stir the solution at 350 rpm for 120 min to mix the solution evenly, thereby obtaining a Ni@UiO-66 / GO (Zr:Ni=3:1) precursor solution;

[0073] Finally, the washed and reserved 3×4×0.5cm CF and the above-mentioned Ni@UiO-66 / GO (Zr∶Ni=3∶1) precursor solution were placed in a 100mL reactor, and the carbon felt was rolled into a column and stood upright in the reactor, completely immersed below the liquid surface of the mixed solution; the hydrothermal reaction was carried out in an oven at a temperature of 120°C for 48h; after the reaction was completed, it was cooled to room temperature, the CF was taken out and washed alternately with N,N-dimethylformamide and methanol, and the washed product was placed in a vacuum and dried at 60°C for 8h to obtain a carbon felt-based Ni@UiO-66 / GO (Zr∶Ni=3∶1) catalytic electrode, named Ni@UiO-66 / GO-CF (Zr∶Ni=3∶

[0074] 1).

[0075] Test the redox property of Ni@UiO-66 / GO-CF (Zr∶Ni=3∶1) catalytic electrode: The redox property of the reduction film was tested by cyclic voltammetry with a scan rate of 10mV / s. The Ni@UiO-66 / GO-CF (Zr∶Ni=3∶1) catalytic electrode was characterized by cyclic voltammetry in 1mol / L sodium sulfate solution. The results are shown in Figure 1 .Depend on Figure 1 It can be seen that the cyclic voltammetry curve of the Ni@UiO-66 / GO-CF (Zr:Ni=3:1) catalytic electrode prepared in Example 1 has an obvious redox peak, indicating that the catalyst has a significant promoting effect on the redox reaction of the electrode.

[0076] Ni@UiO-66 / GO-CF (Zr∶Ni=3∶1) catalytic electrode for treatment of heavy metal wastewater in printed circuit board electroplating process. Performance test of typical metal elements: The structure of the stacked bioelectrochemical system mainly includes anode chamber a, cathode chamber a, anode chamber b, cathode chamber b and proton exchange membrane (PEM) between the anode chamber a, cathode chamber a and air contact oxidation tank are the first system, anode chamber b and cathode chamber b are the second system, and the wastewater first flows through the first system for primary treatment, and then enters the second system for secondary treatment. The stacked bioelectrochemical system uses an iron anode as the main anode. At the same time, the anode chamber is filled with graphite particles and activated carbon particles (filling rate is 90%, among which the volume ratio of graphite particles to activated carbon particles is 1:1, and the particle size is 3-5mm) inoculated with electrogenic bacteria (the main electrogenic bacteria are Gammaproteobacteria and Bacteroidia, with a total concentration of 4g / L) as auxiliary anodes, and Ni@UiO-66 / GO-CF (Zr:Ni=3:1) catalytic electrode is used as the MFC cathode chamber electrode. The anode and cathode are connected with titanium wire, and an external resistor is connected to form a complete circuit. After the system is assembled, anhydrous sodium acetate, ammonium chloride, dipotassium hydrogen phosphate, magnesium sulfate, and calcium chloride are used to provide the organic matter required for the metabolism of electrogenic microorganisms. After the stacked bioelectrochemical system generates electricity stably, mixed metal solutions of different concentrations are prepared as simulated wastewater and directly connected from the anode chamber a to perform performance tests on the system's treatment of copper, nickel, zinc, and cadmium elements (total mixed metal ion concentration is 20-80 mg / L, and the concentration ratio of copper, nickel, zinc, and cadmium elements is 1:1:1:1). The results are shown in Figure 3 .Depend on Figure 3 It can be seen that the Ni@UiO-66 / GO-CF (Zr∶Ni=3∶1) catalytic electrode of Example 1 of the present invention can be effectively applied to the stacked bioelectrochemical system to reduce the copper, nickel, zinc and cadmium elements in the water, the secondary effluent removal rate is above 97.5%, and the effluent concentration of each element reaches the primary emission standard.

[0077] Comparative Example 1

[0078] The same as Example 1, except that the proportion of nickel doping is increased, that is, the molar ratio of zirconium source to nickel source is 2:1, and a carbon felt-based Ni@UiO-66 / GO (Zr:Ni=2:1) ​​catalytic electrode is prepared, named Ni@UiO-66 / GO-CF (Zr:Ni=2:1).

[0079] The redox properties of the Ni@UiO-66 / GO-CF (Zr:Ni=2:1) ​​catalytic electrode were tested in the same manner as in Example 1.

[0080] Comparative Example 2

[0081] The same as Example 1, except that the proportion of nickel doping is increased, that is, the molar ratio of zirconium source to nickel source is 1:1, and a carbon felt-based Ni@UiO-66 / GO (Zr:Ni=1:1) catalytic electrode is prepared, named Ni@UiO-66 / GO-CF (Zr:Ni=1:1).

[0082] The redox properties of the Ni@UiO-66 / GO-CF (Zr:Ni=1:1) catalytic electrode were tested in the same manner as in Example 1.

[0083] Figure 1 The cyclic voltammograms of the carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 and the catalytic electrodes prepared in Comparative Examples 1 and 2 verify the electrochemical catalytic effect of the carbon felt-based Ni@UiO-66 / GO catalytic electrode. The cyclic voltammograms of the carbon felt-based Ni@UiO-66 / GO catalytic electrode relative to the carbon felt substrate show obvious redox peaks, indicating that the addition of the Ni-Zr bimetallic organic framework and GO improves the electrocatalytic performance of the electrode material; in addition, it can be seen from the cyclic voltammograms that the catalytic electrode materials with different nickel doping ratios have an effect on the electrocatalytic performance.

[0084] Figure 2 The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 and the catalytic electrodes prepared in Comparative Examples 1 and 2 show the changes in the ORR starting potential under different Ni doping ratios. It can be seen that the starting potential of the carbon felt-based Ni@UiO-66 / GO catalytic electrode with different nickel doping ratios can be used as a function of the Zr / Ni ratio, which is attributed to supramolecular metal interactions. These interactions promote significant differences in the local electronic structure of the crystalline MOF network and the Zr-Ni catalytic site, thereby reducing the energy barrier of the intermediate catalytic species and increasing the ORR catalytic activity.

[0085] Figure 3 The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 was applied to a stacked bioelectrochemical system to recover different metals in heavy metal ion mixed wastewater (the total mixed metal ion concentration was 20-80 mg / L, and the concentration ratio of copper, nickel, zinc, and cadmium elements was 1:1:1:1), where the horizontal axis represents time in h; the vertical axis represents effluent concentration in mg / L; the hollow symbols and solid symbols represent the primary effluent concentration and the secondary effluent concentration, respectively. As shown in the figure, most of the metal ions can be removed from the mixed wastewater after primary treatment, and the metal ion concentration is further reduced after secondary treatment. For Cu 2+ 、Zn 2+When the total metal concentration is lower than 60 mg / L, the primary effluent concentration and secondary effluent concentration of SSBR are lower than the primary standard concentration of the current national discharge standard (total copper 0.5 mg / L, total zinc 2 mg / L); when the total metal concentration reaches 80 mg / L, the primary effluent concentration is lower than the secondary standard (total copper 1 mg / L, total zinc 5 mg / L), but after secondary treatment, the effluent concentration can reach the primary standard. 2+ Even if the total metal concentration reaches 80 mg / L, the primary effluent concentration already meets the discharge standard (total nickel 1.0 mg / L). 2+ When the total metal concentration is lower than 60 mg / L, the secondary effluent can meet the discharge standard (total cadmium 0.1 mg / L).

[0086] Figure 4 The carbon felt-based Ni@UiO-66 / GO catalytic electrode prepared in Example 1 is used to recover various metals in heavy metal ion mixed wastewater with a total metal ion concentration of 60 mg / L (the concentration ratio of copper, nickel, zinc and cadmium elements in the wastewater is 1:1:1:1), wherein the abscissa represents the type of metal; the ordinate represents the removal efficiency, in %. As can be seen from the figure, the removal rates of copper, nickel, zinc and cadmium elements in the primary effluent are all above 95%; the removal rate of metal elements after the secondary effluent can reach up to 99.4%.

[0087] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode, characterized in that: The following steps are involved: The carbon felt-based Ni@UiO-66 / GO catalytic electrode is prepared by co-loading Ni@UiO-66 and graphene oxide on carbon felt using hydrothermal synthesis; Wherein, the molar ratio of the nickel source to the zirconium source in the Ni@UiO-66 is 1:

3.

2. The method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode according to claim 1, characterized in that: The preparation method comprises the following steps: The nickel source, the zirconium source and terephthalic acid are uniformly mixed in an organic solvent to obtain a Ni@UiO-66 precursor solution; Adding graphene oxide to the Ni@UiO-66 precursor solution and mixing evenly to obtain a mixed solution; The pretreated carbon felt is immersed in the mixed solution, and hydrothermal reaction, cooling, washing and drying are carried out in sequence to obtain the carbon felt-based Ni@UiO-66 / GO catalytic electrode.

3. The method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode according to claim 2, characterized in that: The pretreatment process is: washing the carbon felt in HCl solution, ethanol and deionized water in sequence, and then ultrasonically treating it in deionized water.

4. The method for preparing a carbon felt-based Ni@UiO-66 / GO catalytic electrode according to claim 2, characterized in that: The conditions during the hydrothermal reaction are: the hydrothermal reaction temperature is 120° C. and the reaction time is 48 h; and / or The conditions in the drying process are: vacuum drying at 60°C.

5. A carbon felt-based Ni@UiO-66 / GO catalytic electrode, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the carbon felt-based Ni@UiO-66 / GO catalytic electrode as claimed in claim 5 in the field of preparing bioelectrochemical systems.

7. Application of the carbon felt-based Ni@UiO-66 / GO catalytic electrode as claimed in claim 5 in the field of heavy metal wastewater treatment in printed circuit board electroplating process.

8. A stacked bioelectrochemical system, characterized in that: The carbon felt-based Ni@UiO-66 / GO catalytic electrode described in claim 5 is used as the cathode in the cathode chamber.

9. A stacked bioelectrochemical system according to claim 8, characterized in that: The stacked bioelectrochemical system comprises: The first system and the second system are connected by a pipeline; The first system and the second system both include an anode chamber, a proton exchange membrane and a cathode chamber; wherein the anode in the anode chamber and the cathode in the cathode chamber are connected by a titanium wire and an external resistor to form a loop.

10. A stacked bioelectrochemical system according to claim 9, characterized in that: The anode chamber includes a main anode and an auxiliary anode; Wherein, the main anode is an iron anode; The auxiliary anode is graphite particles and activated carbon particles filled with inoculated electrogenic bacteria.

Citation Information

Patent Citations

  • Method for preparing carbon nano-cage by catalyzing organic ligand by metal ion, prepared carbon nano-cage and application of carbon nano-cage

    CN110272035A

  • Preparation method of polycrystalline hybrid metal catalytic electrode membrane

    CN112678926A

  • Carbon felt-based iron / magnesium / zirconium / nitrogen-doped carbon catalytic electrode and preparation process and application thereof

    CN113506881A

  • Electrochemical detection method for Cd (II) and / or Pb (II) heavy metal ions

    CN117907409A

  • Preparation method of material capable of realizing tetracycline adsorption and visible light degradation

    CN119140072A